The Indians were prosperous : documents of Salish, Pend d'Oreille, and Kootenai Indian history, 1900-1906 - Bigart, Robert; McDonald, Joseph, 1933- (Salish Kootenai College Press, 2021)
"By the end of the nineteenth century the crescendo of economic change facing the Salish, Pend d'Oreille, and Kootenai Indians on the Flathead Indian Reservation in western Montana was reaching a climax. Income was not distributed equally on the reservation, but by 1905 the Indians were basically self-supporting and most of the poorer tribal members had enough to get by. But the surrounding white community cast covetous eyes on tribal assets - especially the land. In 1903, Congressman Joseph Dixon led an assault on the tribes to force the sale of reservation lad to white homesteaders at far below its real value. Tribal leaders realized they were being robbed and protested vigorously - but to no avail. While the tribes were fighting against the coerced allotment, they also fought the State of Montana over taxes and hunting rights"--